Imbalance in Axial-plane Rotator Cuff Fatty Infiltration in Posteriorly Worn Glenoids in Primary Glenohumeral Osteoarthritis: An MRI-based Study. Issue 11 (November 2021) - Hartwell, Matthew J.; Harold, Ryan E.; Sweeney, Patrick T.; Seitz, Amee L.; Marra, Guido; Saltzman, Matthew D.
Abstract: Background: Fatty infiltration of the rotator cuff evaluated with CT has been associated with asymmetric glenoid wear and humeral head subluxation in patients with glenohumeral arthritis. The relationship between rotator cuff pathologic findings and abnormal glenoid wear plays an important role in determining the optimal surgical management of advanced glenohumeral osteoarthritis. Compared with CT, MRI has increased sensitivity for identifying rotator cuff conditions; therefore, prior studies using CT may have underestimated the association between fatty infiltration of the rotator cuff and abnormal glenoid wear. Questions/purposes: (1) Compared with Type A glenoids, which muscles in which Walch subtypes have a greater degree of fatty infiltration using Goutallier scores? (2) What glenoid type is associated with greater imbalance in fatty infiltration, as measured by comparing Goutallier scores between the posterior and anterior rotator cuff muscles? (3) What is the correlation between glenoid version and fatty infiltration of the rotator cuff muscles? (4) Comparing Type B2 and B3 glenoids with Type A glenoids, after accounting for age and sex, is there an increase in fatty infiltration of the infraspinatus muscle? Methods: A total of 129 shoulders from 129 patients undergoing anatomic total shoulder arthroplasty to treat primary glenohumeral osteoarthritis were retrospectively reviewed. Patients had an average age of 66.4 ± 9.3 years and an average BMI of 30.6 ± 6.7 kg/m 2, and 53% (69 of 129) were men. All patients underwent MRI within 12 months before total shoulder arthroplasty to assess glenoid morphology and rotator cuff pathologic findings. Three reviewers assessed the images, and glenoid morphology was assigned using the modified Walch classification system (Types A1, A2, B1, B2, B3, C, and D). Fatty infiltration of the rotator cuff was classified using Goutallier scores. The examiners demonstrated moderate-to-good reliability using these classification systems; the Walch classification system had interrater reliability kappa coefficients (κ) from 0.54 to 0.69 and intrarater reliability κ from 0.60 to 0.64. Goutallier scores using the simplified classification system had interrater reliability κ from 0.64 to 0.68 and intrarater reliability κ from 0.64 to 0.79. Thirty-six percent (46 of 129) of the shoulders had posterior wear patterns (18% [23] were Type B2 glenoids; 18% [23] were Type B3 glenoids). The average Goutallier scores for each rotator cuff muscle were determined, and the amount of fatty infiltration was compared between the various Walch subtypes using independent t-tests. Axial-plane imbalance in fatty infiltration of the rotator cuff was assessed by determining the difference in the average fatty infiltration of the posterior rotator cuff muscles (infraspinatus and teres minor) and anterior rotator cuff muscles (subscapularis) and comparing the differences among the Walch subtypes using independent t-tests. The association between glenoid version and fatty infiltration was assessed using Pearson correlations. Finally, a multivariate logistic regression model was used to assess fatty infiltration of the rotator cuff among the various Walch subtypes while accounting for patient age and sex. Results: Compared with Type A1 glenoids, Type B2 and B3 glenoids had an increased amount of fatty infiltration of the infraspinatus (1.6 ± 0.7 versus 0.7 ± 0.4; mean difference 0.9 [95% CI 0.7-1.2]; p < 0.001 and 1.8 ± 0.4 versus 0.7 ± 0.4; mean difference 1.1 [95% CI 0.9-1.4]; p < 0.001, respectively) and teres minor (1.3 ± 0.7 versus 0.6 ± 0.5; mean difference 0.7 [95% CI 0.4-1.0]; p < 0.001 and 1.6 ± 0.6 versus 0.6 ± 0.5; mean difference 1.0 [95% CI 0.7-1.2]; p < 0.001, respectively). There was greater imbalance in fatty infiltration between the posterior and anterior rotator cuff muscles for Type B2 (0.5 ± 0.3) and B3 (0.6 ± 0.5) glenoids than for Type A1 (0.1 ± 0.3) and A2 (0.1 ± 0.6) glenoids (p < 0.001). Only the infraspinatus's fatty infiltration was strongly correlated with glenoid version (r = 0.64; p < 0.001), while fatty infiltration of the other muscles only correlated weakly or moderately. After accounting for age and sex, fatty infiltration in the infraspinatus was associated with Type B2 (OR 66.1 [95% CI 7.6-577.9]; p < 0.001) and Type B3 glenoids (OR 59.5 [95% CI 5.4-661.3]; p < 0.001) compared with Type A glenoids. Conclusion: Compared with concentric wear, posteriorly worn glenoids had an imbalance in axial-plane rotator cuff fatty infiltration and an increased amount of fatty infiltration of the infraspinatus and teres minor compared with the subscapularis. These imbalances may contribute to the higher rates of failure after anatomic total shoulder arthroplasty in patients with posterior wear compared with those with concentric wear. Future research should be directed toward investigating the temporal relationship of these findings, as well as understanding the clinical outcomes for patients undergoing anatomic total shoulder arthroplasty who have posteriorly worn glenoids with a high degree of fatty infiltration of the posterior rotator cuff musculature. Clinical Relevance: Providers should consider the increased likelihood of higher-grade fatty infiltration of the posterior rotator cuff in the setting of posteriorly worn glenoids, particularly when treating patients without using MRI. These patients have higher rates of failure postoperatively and may benefit from closer monitoring and altered postoperative rehabilitation protocols that target the posterior rotator cuff.